Rancang Bangun Sistem Informasi Ticketing Helpdesk pada DPMPTS Pemprov DKI Jakarta - Alfian Alfian; Yumi Novita Dewi; Firstianty Wahyuhening Fibriany; Harsih Rianto; Adika May Sari (JURIKOM (Jurnal Riset Komputer), 2020)
Implementing Information Technology and Archiving (PSTIK) is a field that has the main task of helping the head of service in leading and carrying out the task of managing information and communication technology. PSTIK is currently not computerized and only relies on whatsapp or telephone connections to address hardware, software or internet network issues called Ticketing Helpdesk. This application allows that at the time of the approval and processing process there is no error in communication at the DPMPTS of the DKI Jakarta Provincial Government. With this Ticketing Helpdesk information system, it is expected to be able to assist operational activities so as to support business processes in the PSTIK sector to be better than the previous system